Morrer nas Morrarias: autonomia, dignidade e formas de solidariedade nas situações de morte no Parque Nacional dos Lençóis Maranhenses - SILVA, Maristhela Rodrigues da (2021)
The events associated with situations of death can be understood as an expression of autonomy, dignity and forms of solidarity between the families that make up the traditional communities of the Lençóis Maranhenses National Park (PNLM). Even before the creation of this entire protection conservation unit, many families already live in the Park, having ways of life based on specific forms of interaction with the biophysical environment. The autonomy of families in these traditional communities and their sociocultural particularities is not expressed only through traditionally carried out activities, such as agriculture, fishing, animal breeding and craft production, but also through associative forms. Among the associative forms of these traditional communities, we highlight the Funerary Associations, created to respond to material and ceremonial needs related to situations of death. Funeral Associations represent an organizational model characterized by the associative participation of family members from different traditional communities in the PNLM. In situations of death, each member contributes a small amount of money and the amount collected by the Associations allows the creation of a fund to cover all the items and expenses indispensable to the funeral rituals of the mourning Family. Taking the functioning of these Funeral Associations as a reference, the thesis aims to understand the foundations of the autonomy of families to deal with situations of death based on the activation of these networks of associates. These initiatives are also interpreted at work as strategies to break, on the one hand, with the forms of welfare dependence on local power and, on the other, to ensure autonomy to respond to material, symbolic, cultural and ceremonial demands related to death situations. Having many other types of associations (religious, residents, mothers clubs), the one that seems to work most effectively is precisely the one that deals with demands related to the end of life, which proposes to solve the needs of related families in cases of death. By dedicating attention to the functioning of Funeral Associations in meeting the demands of families, we can understand not only the ceremonial aspects in relation to situations of death, but also the forms of solidarity and autonomy of families and the moral, economic, legal and symbolic principles that such situations behave.